Mortality Trends In Pre COVID And Pandemic Era In A Tertiary Care Setting - Khan, Hareema Saeed; Dar, Savida Ilyas; Faisal, Tayyaba; Shah, Faridullah; Aslam, Rabbia; Asim, Maheen (Journal of Rawalpindi Medical College, 2023)
Objective: The coronavirus pandemic has emphasized stay-at-home and social distancing policies. Since the beginning of the outbreak of COVID-19, there has been a declining trend of hospital mortality indicating that the pandemic might keep patients from seeking emergency care in a hospital setting. This study was carried out to determine the mortality trends pre-COVID and pandemic periods in a tertiary care hospital. Methods: Study design: Retrospective observational study Place and Duration: 1st January 2019 to December 2021 at Federal Government Polyclinic (FGPC) Hospital Islamabad It was a retrospective review done on death data of pre-COVID (January-December 2019) and pandemic(January 2020-December 2021) period. Data on death was retrieved from medical male and female wards, medical ICU and isolation ward. The mortality rate was measured for both pre-COVID and pandemic periods along with co-morbid for the pandemic period. Descriptive statistics were measured with the SPSS software version. 23. Association with age, gender and mortality was observed using a chi-square test taking p value ≤ 0.05 as significant. Result: In this study of the 366 deaths, the average age of patients in the pre-COVID and pandemic era was57.40±17.910 and 64.31±16.065 respectively. The males and females were 50.9% and 49.1% in the pre-COVID period while 61.5% and 38.5% in the pandemic period. The frequency of deaths was 46.7% in the pre COVID and 53.3% in the pandemic period with a p-value <0.05. Patients with co-morbid died more in the pandemic era. Conclusion: It was observed that hospital mortality trends were in decline during the COVID-19 pandemic in our setting which may be associated with lockdown, decreased access to the hospitals or fear of going to hospital.